Synthesis and biological evaluation of (E)-1-(substituted)-3-phenylprop-2-en-1-ones bearing rhodanines as potent anti-microbial agents. (October 2014) - Song, Ming-Xia; Deng, Xian-Qing; Li, Ya-Ru; Zheng, Chang-Ji; Hong, Lan; Piao, Hu-Ri
Abstract Herein, we report the design, syntheses and in vitro anti-microbial activity of two series of rhodanines with chalcone moiety. Anti-microbial tests showed that some of the synthesized compounds exhibited good inhibition (MIC = 1–8 µg/mL) against multi-drug-resistant Gram-positive organisms, including methicillin resistant and quinolone-resistant Staphylococcus aureus, in which the compound 4g was found to be the most potent with minimum inhibitory concentration (MIC) value of 1 µg/mL against two methicillin-resistant S. aureus.